2015
DOI: 10.1002/cncr.29826
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genomic profiling of 295 cases of clinically advanced urothelial carcinoma of the urinary bladder reveals a high frequency of clinically relevant genomic alterations

Abstract: BACKGROUND In the current study, the authors present a comprehensive genomic profile (CGP)‐based study of advanced urothelial carcinoma (UC) designed to detect clinically relevant genomic alterations (CRGAs). METHODS DNA was extracted from 40 µm of formalin‐fixed, paraffin‐embedded sections from 295 consecutive cases of recurrent/metastatic UC. CGP was performed on hybridization‐captured, adaptor ligation‐based libraries to a mean coverage depth of 688X for all coding exons of 236 cancer‐related genes plus 47 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
69
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 58 publications
(151 reference statements)
6
69
0
3
Order By: Relevance
“…Previous studies have assessed genomic biomarker actionability [40, 41]. These studies included larger numbers of patients and reported high frequencies of clinically actionable genomic markers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have assessed genomic biomarker actionability [40, 41]. These studies included larger numbers of patients and reported high frequencies of clinically actionable genomic markers.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, amplifications of three genes in the FGFR family were mutually exclusive in six samples, suggesting that alterations of these genes might be involved in the oncogenic process. When the genomic profiles of 295 patients with bladder cancer were examined,34 somatic mutations in FGFR3 (21% of patients) and amplifications of FGFR1 (4.7%) were common in bladder cancer. Compared with the relatively infrequent FGFR2 mutations and amplifications (3%, ≤3 cases for each alteration type) in the TCGA bladder dataset (figure 3C), the high and focal amplifications of FGFR2 observed here might be distinguishing features in urachal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CDKN2A, also known as cyclin-dependent kinase inhibitor 2A, codes for two proteins, including p16 an p14arf, both act as tumor suppressors by regulating the cell cycle. The genetic alteration of CDKN2A is most common clinically relevant in the advanced bladder cancer [10]. Both TP53 and CDKN2A alteration contributed to the unfavorable clinical and survival outcomes [11].…”
Section: Discussionmentioning
confidence: 99%